A three-dimensional finite element study on the effect of hydroxyapatite coating thickness on the stress distribution of the surrounding dental implant-bone interface - Hadi Asgharzadeh Shirazi; Mohammadreza Mallakzadeh (Tehran University of Medical Sciences, 2014)
Background and Aims: Hydroxyapatite coating has allocated a special place in dentistry due to its biocompatibility and bioactivity. The purpose of this study was to evaluate the relation between the hydroxyapatite thickness and stress distribution by using finite element method.   Materials and Methods: In this paper, the effect of hydroxyapatite coating thickness on dental implants was studied using finite element method in the range between 0 to 200 microns. A 3D model including one section of mandible bone was modeled by a thick layer of cortical surrounding dense cancellous and a Nobel Biocare commercial brand dental implant was simulated and analyzed under static load in the Abaqus software.   Results The diagram of maximum von Mises stress versus coating thickness was plotted for the cancellous and cortical bones in the range between 0 to 200 microns. The obtained results showed that the magnitude of maximum von Mises stress of bone decreased as the hydroxyapatite coating thickness increased. Also, the thickness of coating exhibited smoother stress distribution and milder variations of maximum von Mises stress in a range between 60 to 120 microns.   Conclusion: In present study, the stress was decreased in the mandible bone where hydroxyapatite coating was used. This stress reduction leads to a faster stabilization and fixation of implant in the mandible bone. Using hydroxyapatite coating as a biocompatible and bioactive material could play an important role in bone formation of implant- bone interface.